The persistence of health inequalities in modern welfare states: The explanation of a paradox - Mackenbach, Johan P. (Social Science & Medicine, 2012)
The persistence of socioeconomic inequalities in health, even in the highly developed ‘welfare states’ of Western Europe, is one of the great disappointments of public health. Health inequalities have not only persisted while welfare states were being built up, but on some measures have even widened, and are not smaller in European countries with more generous welfare arrangements. This paper attempts to identify potential explanations for this paradox, by reviewing nine modern ‘theories’ of the explanation of health inequalities. The theories reviewed are: mathematical artifact, fundamental causes, life course perspective, social selection, personal characteristics, neo-materialism, psychosocial factors, diffusion of innovations, and cultural capital. Based on these theories it is hypothesized that three circumstances may help to explain the persistence of health inequalities despite attenuation of inequalities in material conditions by the welfare state: (1) inequalities in access to material and immaterial resources have not been eliminated by the welfare state, and are still substantial; (2) due to greater intergenerational mobility, the composition of lower socioeconomic groups has become more homogeneous with regard to personal characteristics associated with ill-health; and (3) due to a change in epidemiological regime, in which consumption behavior became the most important determinant of ill-health, the marginal benefits of the immaterial resources to which a higher social position gives access have increased. Further research is necessary to test these hypotheses. If they are correct, the persistence of health inequalities in modern European welfare states can partly be seen as a failure of these welfare states to implement more radical redistribution measures, and partly as a form of ‘bad luck’ related to concurrent developments that have changed the composition of socioeconomic groups and made health inequalities more sensitive to immaterial factors. It is argued that normative evaluations of health inequalities should take these explanations into account, and that a direct attack on the personal, psychosocial and cultural determinants of health inequalities may be necessary to achieve a substantial reduction of health inequalities.
Keywords: Europe; Health inequalities; Trends; Welfare policies; Welfare state